Program Baca Tulis Al-Qur'an; Penerapan Habituasi Pendidikan Karakter pada Anak di Desa Pesisir Kecamatan Sumberasih Kabupaten Probolinggo - Hamid, Abdul; Zaini, Ahmad; Suhartiningsih, Eka (Lembaga Yasin AlSys, 2023)
Character education has an important role in creating quality next generations. One of the efforts made in instilling character values for future generations is through reading and writing Al-Qur'an activities. The purpose of writing this article is to describe how character education is habituated through reading and writing Al-Qur'an programs in Pesisir Village, Kec. Sumberasih Kab. Probolinggo. Based on the preparation and results of trials from the community that was carried out. The author uses a literature review that comes from various sources and scientific journals in the results analysis section. The results of the discussion explained that reading and writing Al-Qur'an activities make children who have habituation so that they can practice Islamic religious teachings and form a religious character. Al-Qur'an reading and writing activities are implemented through a fun approach for children, namely by holding simple games and competitions. Therefore, reading and writing the Qur'an is a reflection by bridging the child's religious character which can be applied from childhood to the end of his life.